2006
DOI: 10.1007/s10803-006-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

[3H]-Flunitrazepam-labeled Benzodiazepine Binding Sites in the Hippocampal Formation in Autism: A Multiple Concentration Autoradiographic Study

Abstract: Increasing evidence indicates that the GABAergic system in cerebellar and limbic structures is affected in autism. We extended our previous study that found reduced [(3)H]flunitrazepam-labeled benzodiazepine sites in the autistic hippocampus to determine whether this reduction was due to a decrease in binding site number (B (max)) or altered affinity (K (d)) to bind to the ligand. Quantitation of hippocampal lamina demonstrated a 20% reduction in B (max) indicating a trend toward a decreased number of benzodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…An increased number of neurons in the cerebral cortex has also been described (24). Furthermore, ligandbinding studies in postmortem tissues have shown that GABA receptors containing the benzodiazepine ligand-binding site are substantially reduced in the hippocampus (5,9) and that AMPA1 receptors are reduced in the cerebellum (7).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An increased number of neurons in the cerebral cortex has also been described (24). Furthermore, ligandbinding studies in postmortem tissues have shown that GABA receptors containing the benzodiazepine ligand-binding site are substantially reduced in the hippocampus (5,9) and that AMPA1 receptors are reduced in the cerebellum (7).…”
Section: Discussionmentioning
confidence: 97%
“…The autism spectrum disorder is a multifaceted syndrome, probably due to many different causes (2)(3)(4). Although these causes are largely unknown, genetic and biochemical studies strongly implicate the GABA and glutamate neurotransmitter receptors, which are, respectively, the principal inhibitory and excitatory receptors in the mammalian brain, including that of humans (5)(6)(7)(8)(9)(10)(11). Despite the immense importance that neurotransmitter receptors have for brain functioning, relatively little is known about the functional properties of receptors of the human brain; almost nothing is known about those of the autistic brain.…”
mentioning
confidence: 99%
“…Recently, the downregulation or alteration of both the GABA A and GABA B receptors in subjects with autism was reported (Fatemi et al 2008(Fatemi et al , 2009, and an autoradiographic study using the [3H]flunitrazepam-labeled benzodiazepine site also suggested there is an alteration in the modulation of the GABA A receptors in the autistic brain (Guptill et al 2007). This accumulating evidence of GABA receptor abnormality indicates that the GABAergic system in the autistic brain is affected.…”
Section: Discussionmentioning
confidence: 99%
“…Blatt et al (2001) reported a reduced binding of benzodiazepines and muscimol in the hippocampus of autistic brains, suggesting a decrease in the number of GABA A receptors. Posterior studies using different concentrations of [H 3 ]flunitrazepan showed that the decrement of benzodiazepine binding was due to reductions of binding sites with no changes in the binding affinity of the receptors (Guptill et al, 2007). Western blot analyses of four GABA A subunits (1-3 and 3) showed reductions of all subunits in parietal cortex, of 1 in frontal cortex and of 1 and 3 in cerebellum of post-mortem autistic brains (Fatemi et al, 2009).…”
Section: Evidence Of Gabaergic Dysfunction In Autismmentioning
confidence: 99%